A STUDY ON THE PRAWN FISHERY OF THE MOUTH OF GULF OF KUTCH WITH SPECIAL REFERENCE TO CERTAIN BIOLOGICAL ASPECTS OF SOME PRAWN SPECIES - Joseph, Antony; Soni, V C (Indian Journal of Fisheries, 2011)
The characteristics of the trawl fishery occurring at the mouth of Gulf of Kutch, with a fishing season starting from the end of September to the first week of May, are described. The commercially important prawns which formed a remarkable part of the prawn fishery at Port Okha were Metapenaeus kutchensis, Parapenaeopsis hardwickii, P. stylifera, Penaeus merguiensis and P. penicillatus. Certain prawns like Solenocera crassicornis, M. monoceros, M. brevicornis, P. semisulcatus and M. affinis were seasonally seen in bulk, while the prawns which poorly represented were P. japonicus and P. sculptilis along with least represented P. monodon and P. canalkulatus. M. kutchensis is the most prominent prawn seen in this area and is the only species which represented the fishery in substantial quantities continuously throughout the season. The maximum representation of different prawn species in the fishery could be noticed during April. Jumbo and medium types of prawns poorly represented the fishery in comparison to tiny type. Overfishing is ruled out and migration of prawns from the fishing grounds noticed. Total prawn landings in Okha area almost doubled within five years. The female prawns always showed higher average mode size than males